2014
DOI: 10.1098/rspb.2014.0701
|View full text |Cite
|
Sign up to set email alerts
|

Maternal exposure to predator scents: offspring phenotypic adjustment and dispersal

Abstract: Predation is a strong selective pressure generating morphological, physiological and behavioural responses in organisms. As predation risk is often higher during juvenile stages, antipredator defences expressed early in life are paramount to survival. Maternal effects are an efficient pathway to produce such defences. We investigated whether maternal exposure to predator cues during gestation affected juvenile morphology, behaviour and dispersal in common lizards (Zootoca vivipara). We exposed 21 gravid female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
123
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(129 citation statements)
references
References 70 publications
4
123
2
Order By: Relevance
“…In contrast to our results, we note that previous work has found that parental experience with risk can increase offspring antipredator behavior under risk (Shine and Downes 1999, Storm and Lima 2010, Giesing et al 2011, Bestion et al 2014. However, unlike our study, offspring in these experiments were exposed to risk for very brief periods of time (,20 minutes).…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our results, we note that previous work has found that parental experience with risk can increase offspring antipredator behavior under risk (Shine and Downes 1999, Storm and Lima 2010, Giesing et al 2011, Bestion et al 2014. However, unlike our study, offspring in these experiments were exposed to risk for very brief periods of time (,20 minutes).…”
Section: Discussioncontrasting
confidence: 99%
“…Not only can predators shape prey growth responses to temperature, but predation risk may have complex impacts on behavioral thermoregulation within and across generations. A recent paper by Bestion et al (2014) shows that gravid female lizards exposed to snake predator cues give birth to offspring that thermoregulate differently, choosing cooler environments and reducing basking behavior. Collectively, these findings have strong implications for our general understanding of how climate warming will impact species interactions.…”
Section: Features Of the Special Issuementioning
confidence: 99%
“…For example, in a diversity of taxa, mothers exposed to predation risk produce offspring with altered phenotypes compared to offspring of unexposed mothers (e.g. birds: Coslovsky & Richner, 2011; daphnia: Agrawal, Laforsch, & Tollrian, 1999; fish: McGhee, Pintor, Suhr, & Bell, 2012; mammals: Sheriff, Krebs, & Boonstra, 2009; insects: Storm & Lima, 2010; reptiles: Bestion, Teyssier, Aubret, Clobert, & Cote, 2014). There is growing appreciation of the ecological and evolutionary significance of such nongenetic transgenerational effects (reviewed in: Badyaev & Uller, 2009; Monaghan, 2008; Sheriff & Love, 2013).…”
mentioning
confidence: 99%